2005
DOI: 10.1002/lapl.200510074
|View full text |Cite
|
Sign up to set email alerts
|

Development of a laser plasma x-ray microscope to observe live hydrated biological specimens

Abstract: Investigating the structure and the function of life ob-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The visualization of dry or hydrated human macrophages and Leydig cells demonstrated that SXCM allows the morphologies of actual intact cells to be viewed and encourages further technological development for biomedical research [45,51,[60][61][62]. This technique also offered the possibility of monitoring the morphological changes in microorganisms (e.g., upon exposure to antibiotics), as was demonstrated for the Gram-negative bacterium, Pseudomonas aeruginosa, and Candida albicans, a yeast, among others [63,64].…”
Section: Cell Imaging With Sxcmmentioning
confidence: 78%
“…The visualization of dry or hydrated human macrophages and Leydig cells demonstrated that SXCM allows the morphologies of actual intact cells to be viewed and encourages further technological development for biomedical research [45,51,[60][61][62]. This technique also offered the possibility of monitoring the morphological changes in microorganisms (e.g., upon exposure to antibiotics), as was demonstrated for the Gram-negative bacterium, Pseudomonas aeruginosa, and Candida albicans, a yeast, among others [63,64].…”
Section: Cell Imaging With Sxcmmentioning
confidence: 78%
“…Specimens used in this work were macrophages (MH-S mouse alveolar macrophage cell line), because of their well known morphological features 7,8 . About 1 μl of the cell suspension in culture medium was directly dropped onto the PMMA.…”
Section: Resultsmentioning
confidence: 99%
“…The duration time of emitted soft x-rays from laser produced plasmas depends on that of the irradiated laser pulses which are generally nano-second or pico-second. This short duration time of laser produced plasmas results in short exposure time to specimens and favorable time to take a snap shot of moving cells with a high spatial resolution 3,4 . In addition, the short exposure time will avoid the effects of radiation damage on the images of living cells.…”
Section: Introductionmentioning
confidence: 99%